Ministerio Público. - Fiscalía del Juzgado 1° Superior. - Medellín, Febrero de 1918 - Jaramillo Arango, Agustín (Estudios de Derecho, 1918)
Ministerio Público. - Fiscalía del Juzgado 1° Superior. - Medellín, Febrero de 1918